High Order Thinking Skills Teaching Innovation: An Analysis onEnglish Teachers’ Understanding and Practices - Pipit Muliyah; Agnira Rekha (English Education Study Program, Faculty of Education and Teachers Training, Tidar Univer, 2020)
The aim of the research was to investigate English teachers’ understanding and its practices in teaching HOTS. This research was conducted from October to November 2019 involved 20 English teachers from state and private school in Majenang and its surroundings. Data about teachers’ understanding was obtained by interviewing the teachers. Meanwhile, the data about its practices was obtained from observation and supervision document from the school principal and supervisor. The result showed that most of English teachers that participated in this research was not clear enough about HOTS and its implementation in teaching and learning process. There were also misunderstanding about designing lesson plan which covered the implementation of teaching HOTS in the classroom. The conclusion indicated that most of older teachers were not clear enough about HOTS and its practices as they are lack of training and information about it. In contrast, most younger participated teachers understood about HOST but they have misconception related to its practices.